The Impact of Election Information Shocks on Populist Party Preferences: Evidence from Germany - Lena Gerling; Kim Leonie Kellermann (ZBW - Leibniz-Informationszentrum Wirtschaft, 2019)
This paper investigates the effect of aggregate-level information shocks regarding support for a populist right-wing party on the individual disposition to report a respective political preference in survey interviews. Despite controversial debates about the social acceptability of its nationalist and xenophobic program, the German AfD has succeeded to enter the state parliaments as well as the federal parliament in the wake of steadily growing support among the electorate. We apply an event-study approach which links election information shocks provided by official results of state-level elections in Germany and the individual disposition to report an AfD preference. Exploiting quasi-random variation in survey interviews conducted closely around state elections, we show that individual exposure to positive election information shocks significantly increases the probability of reporting an AfD vote intention by around 5 percentage points.
Keywords: D71; D72; D91; I24; 330; Voting behavior; populist parties; collective decision-making; contagion effects; information shocks